Molecular Mechanism Involved in the Pathogenesis of Early-Onset Epileptic Encephalopathy - Vitaliti, Giovanna; Pavone, Piero; Marino, Silvia; Saporito, Marco Andrea Nicola; Corsello, Giovanni; Falsaperla, Raffaele (Frontiers in Molecular Neuroscience, 2019)
Recent studies have shown that neurologic inflammation may both precipitate and sustain seizures, suggesting that inflammation may be involved not only in epileptogenesis but also in the development of the drug-resistant profile. Extensive literature data, during these last years, have identified a number of inflammatory markers involved in these processes of "neuroimmunoinflammation" in epilepsy, underlying a key role for other pro-inflammatory cytokines such as: IL-6, IL-17 and IL-17 Receptor (IL-17R) axis, Tumor-Necrosis-Factor Alpha (TNF-α) and Transforming-Growth-Factor Beta (TGF-β), all responsible for the induction of processes of blood-brain barrier (BBB) disruption and inflammation of the Central Nervous System (CNS) itself. Nevertheless, many of these inflammatory biomarkers have been also implicated in other neurologic pathologies, and future perspectives have to address the disease-individuality in order to identify panels of biomarkers that discriminate epilepsies from other diseases and among different epileptic semiology. In this context, markers of blood-brain barrier integrity and disruption are useful tools to determine the sequelae in a variety of neurologic diseases, but how these markers may predict the prognosis and the diagnosis of epileptic disorders is being currently investigated. Herein authors present a review of extensive literature data on the involvement of both systemic and neuronal immune system in the early onset of epileptic encephalopathy.